Validation of language evaluation scale Trivandrum in children aged 3 -6 years attending well baby clinic in a tertiary care hospital - Singraiah, Avinash; Hegde, Pavan; Mendonsa, Hazel D. (International Journal of Contemporary Pediatrics, 2016)
Background: Delay in language development is often an early and most sensitive indicator of intellectual disability. Language delay should be detected in early stages for early intervention, so our study is to validate a simple screening tool to assess language and speech delay in a tertiary care setting. Present study was conducted to validate LEST to use in pediatric clinics to identify delay in language development among children of 3-6years, and to compare LEST and extended receptive expressive emergent scale (Extended REELS). Methods: This was a cross sectional descriptive study done in children aged 3-6 years attending well baby clinic at a tertiary care hospital. Total sample size was 100. After the written informed consent, LEST was applied to all children initially and then extended REELS was administered in the department of speech and hearing. Results: The prevalence of language and speech delay in the present study was 16%. When one item delay was taken as ‘LEST delay’ (test positive), the sensitivity and specificity of LEST was found to be 25% and 80% respectively with a negative predictive value of 85% and Likelihood ratio (LR - negative) of 0.9. When two item delay was taken as ‘LEST delay, sensitivity and specificity, was found to be 44% and 99% respectively with a negative predictive value of 91% and LR (negative) of 0.5. Conclusions: The 16% prevalence of language delay in the children indicates the need for an early identification and for it a simple screening tool like LEST is a must during the routine evaluation of young children in pediatric clinics.